2015
DOI: 10.1371/journal.pone.0115672
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation Analysis by PCR: A Comparison of Two Methods

Abstract: BackgroundKRAS mutation assays are important companion diagnostic tests to guide anti-EGFR antibody treatment of metastatic colorectal cancer. Direct comparison of newer diagnostic methods with existing methods is an important part of validation of any new technique. In this this study, we have compared the Therascreen (Qiagen) ARMS assay with Competitive Allele-Specific TaqMan PCR (castPCR, Life Technologies) to determine equivalence for KRAS mutation analysis.MethodsDNA was extracted by Maxwell (Promega) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…Currently, ARMS PCR has become one of the most important and advanced technologies in the molecular detection of cancer individuals, and its advantages in clinical applications have been widely recognized in industry[17,18]. The detection sensitivity of ARMS method was significantly higher than that of other methods, such as direct sequencing method, which can detect the mutation of 0.1–1.0% gene in samples.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ARMS PCR has become one of the most important and advanced technologies in the molecular detection of cancer individuals, and its advantages in clinical applications have been widely recognized in industry[17,18]. The detection sensitivity of ARMS method was significantly higher than that of other methods, such as direct sequencing method, which can detect the mutation of 0.1–1.0% gene in samples.…”
Section: Discussionmentioning
confidence: 99%
“…11 Sanger capillary sequencing has long been the gold standard for DNA sequence analysis; however, it does not offer the high sensitivity required to detect somatic mutations at allelic frequencies less than ~20%. 12 Numerous comparisons of technology platforms for EGFR 13 14 and KRAS (mainly in CRC [15][16][17][18][19][20][21][22][23] ) mutation testing conclude that quantitative PCR (qPCR)-based methods offer the sensitivity, tissue economy and turnaround time required by physicians to guide treatment decisions. The advent of next-generation sequencing (NGS) platforms offers pathology laboratories an unparalleled insight into the cancer genome including de novo detection of variants as well as known actionable targets.…”
Section: How Might This Impact On Clinical Practice?mentioning
confidence: 99%
“…Compared with ARMS, the most commonly used method in clinical practice in China, CastPCR has improved sensitivity and specificity owing to its oligonucleotide blocker that suppresses the wild-type allele, which does not exist in ARMS (28). Previous studies have demonstrated this in multiple types of malignant tumor (22,38,39). Two previous studies used CastPCR technology to validate detected mutation results obtained by NGS (31,40).…”
Section: Discussionmentioning
confidence: 99%